Organizational And Pedagogical Conditions Of Teaching The Subject Information Communication Technologies And Systems In The Economy (Progress Annals: Journal of Progressive Research, 2025)
The article discusses the organizational and pedagogical conditions necessary for effectively teaching the subject "Information Communication Technologies and Systems in the Economy" in higher education institutions. It examines the integration of digital tools, learning management systems (LMS), interactive teaching formats, and student-centered approaches. The study emphasizes the importance of qualified instructors, updated curricula, infrastructure readiness, and institutional support in fostering competence development in ICT for economics students.